2003
DOI: 10.1111/j.1440-1746.2004.03261.x
|View full text |Cite
|
Sign up to set email alerts
|

New indication for endoscopic treatment of colorectal carcinoma with submucosal invasion

Abstract: The present study showed that endoscopic treatment of early CRC may be considered complete when submucosal invasion beyond 1,500 micron, lymphatic permeation, sprouting, and infiltrating growth are all denied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Although the implication of budding/sprouting in deeply invasive colorectal cancer was first reported in 1989, 25 many studies have also focused on budding/sprouting as a risk factor of lymph node metastasis in T1 colorectal cancer. [12][13][14][15][26][27][28][29][30][31][32] Some investigators refer to findings similar to budding/sprouting as 'unfavorable histology at the invasive front,' 33 'focal dedifferentiation,' 34 or 'tumor cell dissociation,' 35 although the definition is not always consistent. 13,25,32,36 In the evaluation of budding/sprouting, we adopted the definition of Ueno et al 13 because it is widely used and has good reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Although the implication of budding/sprouting in deeply invasive colorectal cancer was first reported in 1989, 25 many studies have also focused on budding/sprouting as a risk factor of lymph node metastasis in T1 colorectal cancer. [12][13][14][15][26][27][28][29][30][31][32] Some investigators refer to findings similar to budding/sprouting as 'unfavorable histology at the invasive front,' 33 'focal dedifferentiation,' 34 or 'tumor cell dissociation,' 35 although the definition is not always consistent. 13,25,32,36 In the evaluation of budding/sprouting, we adopted the definition of Ueno et al 13 because it is widely used and has good reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that differentiation is a predictive factor independent of TB. Previous studies [1][2][3][4][5][6] have shown that the depth of submucosal invasion is a risk factor which can be used for predicting LN metastasis in CRC. A Japanese collaborative study 6 on 865 submucosal invasive CRC cases showed that the rate of LN metastasis is 0% in nonpedunculated T1 CRC if the submucosal invasion depth is less than 1 000 μm.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Previous studies have demonstrated that several pathological factors, such as histological grade, [7][8][9][10][11][12][13] deep invasion into the submucosal layer, [1][2][3][4][5][6] and lymphatic channel involvement [3][4][5]7,8,[10][11][12][13] are pathological predictors for lymph node (LN) metastasis in T1 CRC. However, it is also known that the pathological evaluation has interobserver variability, which cannot be neglected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Recent Japanese studies have demonstrated that stage T1 CRC with a submucosal invasion depth of <1 mm has no possibility of lymph node involvement, provided that other risk factors, e.g., lymphatic channel involvement, venous involvement, and poorly differentiated tumors are absent. [5][6][7][8] Evaluation of the depth of tumor invasion is thus essential when one is deciding the initial treatment for early-stage CRC.…”
mentioning
confidence: 99%